Impact of demographic factors and economic uncertainties on saving behavior - Vong, Kian Sin (2017)
The global saving glut hypothesis points out that the aging population in industrial countries and uncertainty in developing countries has contributed to excess saving. However, this hypothesis has neglected the role of divergent demographic transitions on the saving rates. In addition, the prediction of the aging population in industrial countries increase the saving rate is inconsistent with the life cycle saving hypothesis. Besides, this hypothesis does not suggest which type of uncertainty affect the saving rate. Therefore, this study examines the effect of demographics and various uncertainties on saving rate over the period 1999-2007. The results suggest that the dependency ratios are negative related to saving rate. Thus, the working-age population increase and saving rate would expect to increase. One important policy implication is saving rate trend is predicting to remain high at least in the short- and medium run as dependency ratios declining. Therefore, financial development suggested by the global saving glut hypothesis to reduce saving rate might not be effective. Meanwhile, the results of uncertainties imply that using a single measure of uncertainty to study the effect of uncertainty is inappropriate. One important policy implication is any intervention policy that attempts to mitigate uncertainty has to consider the different effect of uncertainties on the saving rate.